Dialektika Emergency of State dan Tujuan Hukum Dalam Penetapan PERPPU 2/2022 Menjadi Undang-Undang - Arelia, Faraz Almira (Faculty of Law, Universitas Airlangga, 2023)
Abstract This article discusses how the dialectic of emergency of state with the principle of legal objectives against the stipulation of Government Regulation instead of Law (PERPPU) Number 2 of 2022 on Job Creation into Law Number 6 of 2023. The research method uses a normative legal research model. The results showed that forming regulations on job creation in Indonesia is a dynamic aspect of policy formulation for the community, either pro or con. The state's emergency is interpreted subjectively, where the President has the authority to issue PERPPU if the country is in a dangerous situation to prevent a legal vacuum. The lawful purpose of the stipulation does not only stop at the aspect of legal certainty but needs to pay attention to the principles of justice and expediency as the purpose of the nation and state. Keywords: Government Regulation Liew of Law, Job Creation, Emergency State, Purpose of Law. Abstrak Artikel ini membahas bagaimana dialektika emergency of state dengan prinsip tujuan hukum terhadap penetapan Peraturan Pemerintah Pengganti Undang-Undang (PERPPU) Nomor 2 Tahun 2022 tentang Cipta Kerja menjadi Undang-Undang Nomor 6 Tahun 2023. Metode penelitian menggunakan model penelitian hukum normatif. Hasil penelitian menunjukan bahwa pembentukan peraturan tentang cipta kerja di Indonesia merupakan aspek dinamis dalam perumusan kebijakan terhadap masyarakat baik pro atau kontra. Emergency of state ditafsirkan secara subjektif, dimana Presiden memiliki kewenangan untuk menerbitkan PERPPU apabila negara berada di situasi berbahaya untuk mencegah kekosongan hukum. Tujuan hukum penetapan tersebut tidak hanya berhenti pada aspek kepastian hukum semata, namun perlu memperhatikan prinsip keadilan serta kemanfaatan sebagaimana tujuan berbangsa dan bernegara. Keywords: Perppu; Cipta Kerja; Emergency State;Tujuan Hukum.